2009
DOI: 10.1104/pp.108.133967
|View full text |Cite
|
Sign up to set email alerts
|

Gene and Metabolite Regulatory Network Analysis of Early Developing Fruit Tissues Highlights New Candidate Genes for the Control of Tomato Fruit Composition and Development      

Abstract: Variations in early fruit development and composition may have major impacts on the taste and the overall quality of ripe tomato (Solanum lycopersicum) fruit. To get insights into the networks involved in these coordinated processes and to identify key regulatory genes, we explored the transcriptional and metabolic changes in expanding tomato fruit tissues using multivariate analysis and gene-metabolite correlation networks. To this end, we demonstrated and took advantage of the existence of clear structural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
203
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(210 citation statements)
references
References 89 publications
3
203
0
4
Order By: Relevance
“…Figure 4B, representing the local pattern of LD around the peak SNP, suggests that the LD level is relatively low in this genomic region. From a functional point of view, citrate and malate are two organic compounds found in most ripe fruits (Etienne et al, 2013) and have been demonstrated to be highly correlated with many important regulators of ripening in studies that have investigated early fruit development (Mounet et al, 2009;Centeno et al, 2011). This result suggests that, in this study, we were able to identify a peak SNP that is located near one or several putative candidate gene(s) playing a crucial role in the citrate and malate metabolic pathways.…”
Section: Gwa For Metabolic Traitssupporting
confidence: 59%
“…Figure 4B, representing the local pattern of LD around the peak SNP, suggests that the LD level is relatively low in this genomic region. From a functional point of view, citrate and malate are two organic compounds found in most ripe fruits (Etienne et al, 2013) and have been demonstrated to be highly correlated with many important regulators of ripening in studies that have investigated early fruit development (Mounet et al, 2009;Centeno et al, 2011). This result suggests that, in this study, we were able to identify a peak SNP that is located near one or several putative candidate gene(s) playing a crucial role in the citrate and malate metabolic pathways.…”
Section: Gwa For Metabolic Traitssupporting
confidence: 59%
“…The biological significance of metabolite-transcript correlations has usually been considered to reflect simple or complex associations between them (Mounet et al, 2009). We investigated the correlation between ReCHS gene expression profiles and the accumulation of metabolites (total flavonoids and total anthraquinones) to decipher the possible involvement of two divergent ReCHS paralogs toward either of the secondary metabolite groups.…”
Section: Correlation Between Rechs Transcript Levels and Metabolite Amentioning
confidence: 99%
“…Samples were fixed and embedded in paraffin as previously described (Mounet et al, 2009). Eight-micrometer slides of exocarp were stained using saturated and filtered Sudan Red solution in ethanol.…”
Section: Light Microscopymentioning
confidence: 99%
“…The cDNA sizing was performed after a total RNA extraction from 100 mg fresh weight and a reverse transcription, as previously described (Mounet et al, 2009;Girard et al, 2012). The amplification was performed using GDSL2-cDNA4F and GDSL2-cDNA5R primers.…”
Section: Pcr and Quantitative Reverse-transcription Pcr Analysis Of Smentioning
confidence: 99%